Pathway from diagnosis to therapy in cancer pain (Percorso diagnostico terapeutico (PTDA) nel dolore oncologico) - Salvatore Palazzo, MD; William Raffaeli, MD; Silvia Ceniti, MD; Francesco Amato, MD (Publiediting, 2013)
The authors present in detail the proposal of a quality improvement project for cancer pain therapies.The project should be implemented through diagnostic and therapeutic pathways and the setting up of a community of oncologists and cancer pain experts.